Hepatobiliary Manifestations of Inflammatory Bowel Disease. Issue 6 (2000) - Memon, Mohammed Iqbal; Memon, Breda; Memon, Muhammed Ashraf
Abstract : Hepatobiliary manifestations occur quite frequently in patients suffering from chronic ulcerative colitis and Crohn's disease and carry with them considerable morbidity and mortality. Although the true incidence is difficult to determine, clinically, significant hepatobiliary disease occurs in 5%–10% of patients. At the present moment, the aetiology and pathogenesis of inflammatory bowel disease and its systemic manifestations remains speculative. For those hepatobiliary manifestations that respond to therapy of the underlying bowel disease, medical and/or surgical therapy must be aggressively pursued. More urgent research is required towards understanding the underlying cause(s) of the primary bowel disease and its systemic manifestations in order to improve the overall management of this condition.